Screening of Antioxidative Properties and Inhibition of Inflammation-Linked Enzymes by Aqueous and Ethanolic Extracts of Plants Traditionally Used in Wound Healing in Poland - Marta Mainka; Monika E. Czerwińska; Ewa Osińska; Maria Ziaja; Agnieszka Bazylko (Antioxidants, 2021)
A wide range of plant-derived preparations have been used against skin inflammatory disorders and as wound healing agents in traditional medicine. The purpose of the study was to determine the antioxidant activity of aqueous and 70% ethanolic extracts from eleven species of plants traditionally used in Poland to treat inflammatory skin diseases. The ability of extracts to scavenge 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), hydrogen peroxide (H2O2), and superoxide anion (O2•−), was studied. In non-cellular studies, an analysis of the anti-inflammatory effect on the activity of enzymes, such as hyaluronidase (HYAL) and lipoxygenase (LOX), was also performed. The chemical profiles of the most active extracts were achieved by applying the UHPLC-DAD-MSn method, and the sum of polyphenols in all tested extracts was determined by the colorimetric method with the Folin–Ciocalteu reagent. The scope of the extracts’ influence on enzyme activity was significantly lower than their antioxidant activity. All extracts have shown high activity in free radical scavenging against DPPH. The ethanolic extracts have shown high potential to scavenge H2O2. The study of composition showed that the main components of the tested extracts were flavonoids, such as luteolin, apigenin, kaempferol, and quercetin derivatives, as well as caffeoylquinic acids, caffeic acid, and its conjugates.